Ответы и объяснения

Лучший Ответ!
2012-01-03T19:51:42+04:00

Выражение: (z^m)^2*z^3/z^m

 

Ответ: z^(m+3)

 

Решаем по действиям:

1) (z^m)^2=z^(m*2)

  (z^m)^2=z^(m*2)

2) z^(m*2)*z^3=z^(m*2+3)

3) z^(m*2+3)/z^m=z^(m+3)

  z^(m*2+3)/z^m=z^(m*2+3-m)

  3.1) m*2-m=1*m

 

Решаем по шагам:

1) z^(m*2)*z^3/z^m

  1.1) (z^m)^2=z^(m*2)

      (z^m)^2=z^(m*2)

2) z^(m*2+3)/z^m

  2.1) z^(m*2)*z^3=z^(m*2+3)

3) z^(m+3)

  3.1) z^(m*2+3)/z^m=z^(m+3)

      z^(m*2+3)/z^m=z^(m*2+3-m)

    3.1.1) m*2-m=1*m

2012-01-03T20:13:06+04:00

1) (z^m)^2=z^(m*2)

  (z^m)^2=z^(m*2)

2) z^(m*2)*z^3=z^(m*2+3)

3) z^(m*2+3)/z^m=z^(m+3)

  z^(m*2+3)/z^m=z^(m*2+3-m)

  3.1) m*2-m=1*m